2019
DOI: 10.1016/j.ecoenv.2018.10.095
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and subcellular distribution of aluminum in a marine diatom

Abstract: Aluminum (Al) is widespread in the environment including the ocean. The effects of Al on marine organisms have attracted more and more attention in recent years. However, the mechanisms of uptake of Al by marine organisms and the subcellular distribution of Al once assimilated are unknown. Here we report the uptake and subcellular distribution of Al in a marine diatom Thalassiosira weissflogii. Short-term (< 120 min) uptake experiments showed that the Al uptake rate by the diatom was 0.033 ± 0.013 fmol/cell/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…The higher growth rates observed in the Al-enriched treatments during this phase, when phosphorus limitation occurred, are likely related to the proposed mechanism of Al-facilitated DOP utilization (Zhou et al 2016;Fig.1). The diatoms may also use polyphosphate bound to the internalized Al in diatom cells, as our recent study showed that most (69%) of the internalized Al in T. weissflogii cells was bound as inorganic granules, likely in polyphosphate bodies (Liu et al 2019).…”
Section: Beneficial Effects Of Al On the Growth And Carbon Fixation Of Marine Phytoplanktonmentioning
confidence: 97%
See 2 more Smart Citations
“…The higher growth rates observed in the Al-enriched treatments during this phase, when phosphorus limitation occurred, are likely related to the proposed mechanism of Al-facilitated DOP utilization (Zhou et al 2016;Fig.1). The diatoms may also use polyphosphate bound to the internalized Al in diatom cells, as our recent study showed that most (69%) of the internalized Al in T. weissflogii cells was bound as inorganic granules, likely in polyphosphate bodies (Liu et al 2019).…”
Section: Beneficial Effects Of Al On the Growth And Carbon Fixation Of Marine Phytoplanktonmentioning
confidence: 97%
“…receiving high dust deposition (40 nM) (Menzel Barraqueta et al 2019), the upper limit of dissolved Al in natural seawater (200 nM), and the concentration in estuarine waters (2000 nM), respectively (Zhou et al 2016). All the added Al will remain in the dissolved form in the culture media (Liu et al 2019) ) (Zhou et al 2018b). Aluminum will not form complexes significantly with EDTA or phosphate in alkaline seawater (Zhou et al 2016;Liu et al 2019).…”
Section: Preparation Of Reagents and Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…grown in the presence of 2 μM Al 3+ as found by TGA appeared to be approximately 60% higher. The role of mineral particles inside the cell, most likely being metal-polyphosphate granules, has been suggested to be a tolerance mechanism for many organisms including diatoms to detoxify Al and other hard cations 28,46 . Therefore, the formation of the particles within the cell in the presence of Al 3+ which contained a high amount of P, O, Si and Al (Fig.…”
Section: Macroscopic Al Distribution and Atomic Coordination Environmmentioning
confidence: 99%
“…Most notably, Al incorporation into frustules of several diatom species has shown a significantly enhanced hydrolysis resistance compared to their Al-free types 26,27 . To date, the internalization of Al into the diatom cells has been investigated from a biological perspective in which Al is distributed within the cell at different subcellular compounds such as granules, debris, organelles, and proteins 28,29 . From the material science perspective exploring the effect of inorganic constituents like Al on the frustule pore size or thickness and the parameters controlling silicification are important too.…”
mentioning
confidence: 99%